Negative electrode for lithium secondary battery and lithium secondary battery comprising the same

CN116711103BActive Publication Date: 2026-10-30LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280008731.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-22
Filing Date
2022-11-15
Publication Date
2026-10-30
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

如果这样的现象持续下去,则电解质中的硝酸锂含量最终会降低到一定水平,从而可能存在电池的寿命迅速降低的问题

Benefits of technology

[0030]根据本发明,通过使用含有形成在其内部和表面上的锂化合物的锂基材作为锂二次电池的负极,可以改善锂二次电池的寿命特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116711103B_ABST
    Figure CN116711103B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery comprising the same, and more particularly, to a negative electrode for a lithium secondary battery capable of improving the life characteristics of a lithium secondary battery, and a lithium secondary battery comprising the same, in which a lithium foil contained in the negative electrode comprises LiNO3, and the LiNO3 is uniformly contained inside and on the surface of the lithium foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the priority benefit of Korean Patent Application No. 2021-0160928, filed on November 22, 2021, the entire contents of which are incorporated herein by reference.

[0002] This invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery containing the same. Background Technology

[0003] Lithium-ion batteries using lithium metal as the negative electrode active material are attracting attention as a next-generation battery that can replace lithium-ion batteries using carbon-based negative electrode active materials such as graphite, due to their high theoretical capacity (3860 mAh / g) and low standard reduction potential (-3.040 V relative to SHE).

[0004] However, the high reactivity of lithium metal, coupled with its lower coulombic efficiency, shorter lifespan, and lower safety compared to lithium-ion batteries, has delayed the commercialization of lithium metal batteries.

[0005] Specifically, during the operation of lithium secondary batteries using lithium metal as the negative electrode active material, lithium dendrites and dead lithium are generated on the surface of the lithium metal negative electrode. These materials can form a passivation layer (solid electrolyte interface, SEI) on the surface of the lithium metal negative electrode, and the process of these materials easily breaking and forming can be repeated.

[0006] Therefore, the negative electrode active material that can participate in the electrochemical reaction is gradually lost, thereby reducing the coulombic efficiency and shortening the life of the lithium metal battery.

[0007] Furthermore, lithium dendrites growing from the surface of the lithium metal anode can penetrate the separator and reach the cathode, thereby causing an internal short circuit in the lithium metal battery, which is directly related to safety issues such as fire and explosion.

[0008] Therefore, in order to ensure battery life and safety by suppressing dendrite growth on the surface of lithium metal anodes, various technologies have been developed to form a protective layer on the surface of lithium anodes.

[0009] Korean Patent Publication No. 2020-0132491 discloses a lithium metal anode treated with lithium nitrate (LiNO3). This anode forms a protective surface layer on the surface of the lithium metal film with an increased amount of lithium oxide through a chemical reaction between the lithium metal film and the lithium nitrate. However, if the electrolyte contains lithium nitrate, it rapidly decomposes on the surface of the lithium metal anode during battery charging / discharging to form a solid electrolyte interface (SEI). If this continues, the lithium nitrate content in the electrolyte will eventually decrease to a certain level, potentially leading to a rapid reduction in battery life.

[0010] Therefore, there is a need to develop technologies that can improve the lifespan performance of lithium secondary batteries by preventing the rapid decrease in lithium nitrate content in the electrolyte, even when the battery is repeatedly charged and discharged.

[0011] [Existing Technical Documents]

[0012] [Patent Literature]

[0013] (Patent Document 1) Korean Patent Publication No. 2020-0132491 Summary of the Invention

[0014] Technical issues

[0015] The inventors of this invention have confirmed that by adding LiNO3 to lithium foil used as the negative electrode for lithium secondary batteries, and by uniformly containing LiNO3 inside and on the surface of the lithium foil, the life characteristics of lithium secondary batteries can be improved.

[0016] Therefore, one object of the present invention is to provide a negative electrode for lithium secondary batteries and a method for manufacturing the same, wherein the negative electrode can improve the life characteristics of the battery.

[0017] Another object of the present invention is to provide a lithium secondary battery comprising a negative electrode for a lithium secondary battery, the lithium secondary battery having excellent discharge capacity and lifespan characteristics.

[0018] Technical solution

[0019] To achieve the above objectives, the present invention provides a negative electrode for a lithium secondary battery, the negative electrode comprising a lithium substrate and lithium compounds formed on and inside the lithium substrate.

[0020] The lithium compound may include at least one of the following: LiNO3, LiF, LiCl, Li2S, Li2CO3, and Li2O.

[0021] The content of the lithium compound relative to the total weight of the lithium substrate can be more than 0% by weight and less than 30% by weight.

[0022] The lithium substrate can be lithium foil.

[0023] The thickness of the lithium substrate can be from 5 to 500 μm.

[0024] The present invention also provides a method for manufacturing a negative electrode for a lithium secondary battery, the method comprising the steps of: (S1) manufacturing a lithium ingot by adding a lithium compound to molten lithium; and (S2) rolling the lithium ingot to manufacture a lithium substrate, the lithium substrate containing the lithium compound formed on and inside its surface.

[0025] The lithium compound can be a lithium compound powder.

[0026] The present invention also provides a lithium secondary battery comprising a positive electrode, a negative electrode for a lithium secondary battery as described above, a separator, and an electrolyte.

[0027] The positive electrode may contain sulfur.

[0028] The lithium secondary battery can be a lithium-sulfur secondary battery.

[0029] Beneficial effects

[0030] According to the present invention, the life characteristics of lithium secondary batteries can be improved by using a lithium substrate containing lithium compounds formed therein and on its surface as the negative electrode of a lithium secondary battery. Attached Figure Description

[0031] Figure 1 This is a scanning electron microscope (SEM) image of the lithium foil containing LiNO3 prepared in Example 1.

[0032] Figure 2 The energy dispersive X-ray spectroscopy (EDS) results of the lithium foil containing LiNO3 prepared in Example 1 are shown.

[0033] Figure 3 This is a graph showing the life performance measurement results of lithium-ion batteries manufactured using the lithium foils in Example 1 and Comparative Example 1, respectively.

[0034] Figure 4 The graph shows the life performance measurement results of lithium-sulfur secondary batteries manufactured using the lithium foils in Example 1, Comparative Example 1, and Comparative Example 2, respectively. Detailed Implementation

[0035] The invention will be described in more detail below to aid in understanding it.

[0036] The terms or words used in this specification and claims should not be construed as being limited to ordinary or dictionary terms, but should be interpreted in accordance with the meaning and concept of the technical idea of ​​the invention, based on the principle that the inventor is able to properly define the concepts of the terms in order to describe his invention in the best possible way.

[0037] Negative electrode for lithium secondary batteries

[0038] This invention relates to a negative electrode for a lithium secondary battery. The negative electrode for the lithium secondary battery comprises a lithium substrate and lithium compounds formed on and within the lithium substrate.

[0039] According to one embodiment of the present invention, the negative electrode for the lithium secondary battery may be a lithium foil containing lithium nitrate (LiNO3) on its surface and inside.

[0040] In this invention, since the lithium compound is uniformly present on the surface and inside the lithium substrate, the lithium compound does not decompose rapidly but dissolves slowly as the battery is repeatedly charged / discharged, thereby improving lifespan characteristics.

[0041] Furthermore, the lithium compound can be a material that helps lithium grow uniformly when reacting with the lithium substrate to form a solid electrolyte interface (SEI). For example, the lithium compound may contain at least one of the following: LiNO3, LiF, LiCl, Li2S, Li2CO3, and Li2O, and LiNO3 may be used to improve battery life characteristics.

[0042] In this invention, the content of the lithium compound relative to the total weight of the lithium substrate can be more than 0% by weight and less than 30% by weight. Specifically, the content of the lithium compound can be more than 0% by weight, more than 0.5% by weight, more than 1% by weight, or more than 1.5% by weight, and less than 5% by weight, less than 10% by weight, less than 20% by weight, or less than 30% by weight. If the content of the lithium compound is 0% by weight, the effect of improving the life characteristics of the lithium secondary battery may not be significant. If the content of the lithium compound exceeds 30% by weight, the resistance of the battery increases and overvoltage may occur, thereby deteriorating the life characteristics of the battery.

[0043] In this invention, the lithium compound may be uniformly contained within and on the surface of the lithium substrate.

[0044] The lithium compound can be contained in the interior and surface of the lithium substrate in powder form. Furthermore, in the manufacturing process of the negative electrode for lithium secondary batteries, the lithium compound can be uniformly formed and contained within the interior and surface of the lithium substrate due to the steps of adding and dispersing the lithium compound after melting lithium.

[0045] If the lithium compound forms only on the surface of the lithium foil, it is easily decomposed by the electrolyte during battery operation, and the battery's life characteristics may deteriorate.

[0046] Furthermore, if the lithium compound is contained only inside the lithium foil, the overvoltage increases and the initial degradation accelerates, which may eventually lead to a deterioration in the battery's lifespan characteristics.

[0047] In this invention, the thickness of the lithium substrate can be from 5 to 500 μm. Specifically, the thickness of the lithium substrate can be 5 μm or more, 10 μm or more, 30 μm or more, or 50 μm or more, and less than 100 μm, 300 μm or less, or 500 μm. If the lithium substrate is too thin, the performance and lifespan characteristics of the battery may deteriorate. If the lithium substrate is too thick, there may be a problem of product thickness.

[0048] In this invention, the lithium substrate can also be used by laminating it onto the negative electrode current collector.

[0049] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the relevant battery. For example, copper, stainless steel, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloys, etc., can be used as the negative electrode current collector. The negative electrode current collector can be in various forms, such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabrics, etc., with micro-uneven surfaces.

[0050] Manufacturing method of negative electrode for lithium secondary batteries

[0051] The present invention also relates to a method for manufacturing a negative electrode for a lithium secondary battery. The method for manufacturing a negative electrode for a lithium secondary battery includes the following steps: (S1) manufacturing a lithium ingot by adding a lithium compound to molten lithium; and (S2) rolling the lithium ingot to manufacture a lithium substrate, the lithium substrate containing the lithium compound formed on and inside its surface.

[0052] The steps of the method for manufacturing a negative electrode for a lithium secondary battery according to the present invention will be described in detail below.

[0053] In this invention, in step (S1), lithium ingots can be manufactured by adding a lithium compound to molten lithium.

[0054] The molten lithium can be prepared by heating lithium at a temperature between 300°C and 600°C. Specifically, the heating temperature can be above 300°C, above 350°C, or above 400°C, and below 500°C, below 550°C, or below 600°C. If the heating temperature is below 300°C, the lithium may not melt sufficiently, and if the heating temperature exceeds 600°C, the lithium may denature.

[0055] The lithium compound can be in the form of lithium compound powder. Considering the uniform dispersion when added to the molten lithium, the size of the lithium compound powder can be from 500 nm to 10 μm. In this case, the size can be the length of the longest axis of the powder.

[0056] In this invention, in step (S2), lithium foil containing lithium compounds can be manufactured by rolling the lithium ingot.

[0057] There are no particular limitations on the pressure during the calendering process, as long as it is sufficient to form a substrate such as a foil, and the calendering process can be performed using known extrusion and / or calendering processes. For example, the calendering process can be performed using a rotary roll or flatbed press.

[0058] In this invention, when a negative electrode current collector is used, after step (S2), a further step of stacking the lithium foil on the negative electrode current collector may be included.

[0059] Furthermore, there are no particular limitations on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the relevant battery. For example, copper, stainless steel, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, silver, etc., aluminum-cadmium alloys, etc., can be used as the negative electrode current collector. In addition, similar to the positive electrode current collector, the negative electrode current collector can be in various forms, such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabrics, etc., with micro-uneven surfaces.

[0060] Lithium secondary batteries

[0061] The present invention also relates to a lithium secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte.

[0062] negative electrode

[0063] In the lithium secondary battery according to the present invention, the negative electrode is the same as the negative electrode used in the lithium secondary battery described above.

[0064] positive electrode

[0065] In the lithium secondary battery according to the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.

[0066] The positive electrode active material layer may include a positive electrode active material, a binder, and a conductive material.

[0067] The positive electrode active material may contain elemental sulfur (S8), chalcogenides, or mixtures thereof, and the chalcogenides may specifically be Li2S. n (n=1), organic sulfur compounds or sulfur-carbon composite materials (C2S) x ) n (x = 2.5 to 50, n = 2). Furthermore, in the positive electrode active material, the sulfur-carbon composite material reduces the outflow of sulfur into the electrolyte and is a mixture of carbon material and sulfur, thereby increasing the conductivity of the sulfur-containing electrode.

[0068] The sulfur-carbon composite material may contain sulfur and carbon materials, specifically, it may contain sulfur and carbon materials in a weight ratio of 55 to 90:45 to 10. If the weight ratio of sulfur and carbon materials contained in the sulfur-carbon composite material is satisfied, the battery capacity can be improved while maintaining conductivity.

[0069] Furthermore, relative to the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite material can be between 60 and 95% by weight. Specifically, the content can be 60% or more, 70% or more, or 80% or more, or the content can be less than 93% by weight, 94% or less, or 95% by weight. If the content is below the above range, the battery performance may deteriorate. If the content exceeds the above range, the content of binders and / or metal oxide additives other than the positive electrode active material is relatively reduced, thus durability may decrease, or the effect of improving positive electrode capacity or battery life characteristics may be insignificant.

[0070] Furthermore, in the sulfur-carbon composite material, the sulfur can be selected from the group consisting of elemental sulfur (S₈), sulfide compounds, or sulfur-carbon composite materials. Specifically, the sulfide compounds can be Li₂S. n (n=1), organic sulfur compounds or sulfur-carbon polymers (C2S) x ) n (x = 2.5 to 50, n = 2).

[0071] Furthermore, in the sulfur-carbon composite material, the carbon material can be a porous carbon material, and it can typically be prepared by carbonizing various carbon material precursors.

[0072] The porous carbon material may contain non-uniform pores, the average diameter of which may be in the range of 1 to 200 nm, specifically above 1 nm, above 5 nm, or above 10 nm, and below 100 nm, below 150 nm, or below 200 nm. Furthermore, the porosity of the porous carbon material may be in the range of 10% to 90% of the total volume of the porous carbon, specifically above 10%, above 15%, or above 20%, and below 70%, below 80%, or below 90%. If the average diameter and porosity of the pores are less than the above ranges, the pore size is only at the molecular level, making sulfur impregnation impossible. Conversely, if the average diameter and porosity of the pores exceed the above ranges, the mechanical strength of the porous carbon material is weakened, which is undesirable for applications in electrode manufacturing processes.

[0073] The porous carbon material can be in the form of spheres, rods, needles, plates, tubes or blocks, and can be used without restriction, as long as it is commonly used.

[0074] The porous carbon material may have a porous structure or a high specific surface area, and may be any porous carbon material conventionally used in the art. For example, the porous carbon material may be, but is not limited to, at least one selected from the group consisting of: graphite; graphene; carbon black such as Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); and activated carbon. Preferably, the porous carbon material may be graphite.

[0075] In addition, the adhesive may be styrene-butadiene rubber (SBR) / carboxymethyl cellulose (CMC), poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, poly(methyl methacrylate), polyvinylidene fluoride, polyhexafluoropropylene and polyvinylidene fluoride copolymer (product name: Kynar), poly(ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polystyrene, polyacrylic acid, and its derivatives, blends and copolymers thereof.

[0076] Furthermore, relative to the total weight of the positive electrode active material layer, the content of the binder can be 1 to 20% by weight, preferably 3 to 18% by weight, and more preferably 5 to 15% by weight. If the content of the binder is within the above range, the bonding force between the positive electrode active materials or between the positive electrode active material and the current collector is greatly improved, and capacity characteristic degradation can be prevented. Furthermore, it is expected that the dissolution of polysulfides can be suppressed through the interaction between the polysulfides and specific functional groups in the polymer chain used as the binder. If the content of the binder exceeds the above range, the battery capacity may decrease.

[0077] In addition, the conductive material may be included to ensure the movement path of lithium ions in the positive electrode.

[0078] The conductive material may be at least one selected from the group consisting of: carbon black selected from Super P, Danka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black and thermal cracking black; carbon derivatives selected from carbon nanotubes and fullerenes; conductive fibers selected from carbon fibers and metal fibers; fluorides; metal powders selected from aluminum and nickel powders; and conductive polymers selected from polyaniline, polythiophene, polyacetylene and polyphenols.

[0079] The content of the conductive material relative to the total weight of the positive electrode active material can be from 1% to 20% by weight. Specifically, the content of the conductive material can be more than 1% by weight, more than 3% by weight, or more than 5% by weight, and can be less than 15% by weight, less than 18% by weight, or less than 20% by weight. If the content of the conductive material is less than the above range, it is difficult to form and maintain a conductive structure and lithium-ion migration path throughout the entire positive electrode active material layer, making the effect of increasing battery discharge capacity and improving overvoltage potentially insignificant. If the content of the conductive material exceeds the above range, it may actually reduce battery life.

[0080] As described above, the positive electrode can be prepared by mixing a positive electrode active material, a binder, and a conductive material in a solvent to prepare a positive electrode slurry, and then coating the positive electrode slurry onto a positive electrode current collector and drying it.

[0081] The solvent used to prepare the positive electrode slurry can be at least one selected from the group consisting of: water (distilled water), methanol, ethanol, isopropanol, acetone, dimethyl sulfoxide, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, acetic acid, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate. In particular, the use of water (distilled water) or anhydrous alcohol-based solvents is desirable because they can prevent damage to the positive electrode active material.

[0082] There are no particular restrictions on the concentration of the positive electrode slurry, as long as it allows for a smooth coating process.

[0083] diaphragm

[0084] In this invention, the diaphragm can be formed from a porous substrate, and the porous substrate can be any porous substrate conventionally used in electrochemical devices. For example, polyolefin-based porous membranes or nonwoven fabrics can be used as the porous substrate, but are not particularly limited thereto.

[0085] Examples of the polyolefin-based porous membranes may include membranes formed from olefin polymers, such as individual substances or mixtures thereof: polyethylene such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene and ultra-high molecular weight polyethylene, polypropylene, polybutene and polypentene.

[0086] In addition to the aforementioned polyolefin-based nonwoven fabrics, the nonwoven fabric may also include, for example, nonwoven fabrics formed from the following substances alone or mixtures thereof: polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalate. The structure of the nonwoven fabric may be a spunbond nonwoven fabric or a meltblown nonwoven fabric composed of long fibers.

[0087] There is no particular limitation on the thickness of the porous substrate, but it can be from 1 μm to 100 μm or from 5 μm to 50 μm.

[0088] There are no particular limitations on the size and porosity of the pores present in the porous substrate, but they can be from 0.001 μm to 50 μm and from 10% to 95%, respectively.

[0089] electrolyte

[0090] In this invention, the electrolyte can be a non-aqueous electrolyte, and the electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. There are no particular limitations on the lithium salt, as long as it can be conventionally used in electrolytes for lithium secondary batteries. For example, the lithium salt can be at least one selected from the group consisting of: LiFSI, LiPF6, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB... 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiPF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane and lithium 4-phenylborate.

[0091] The organic solvent contained in the non-aqueous electrolyte can be any organic solvent conventionally used in electrolytes for lithium secondary batteries, and can be used alone or in combination of two or more of them, such as ethers, esters, amides, linear carbonates, cyclic carbonates, etc. Representatively, it may include carbonate compounds as cyclic carbonates, linear carbonates, or slurries thereof.

[0092] Specific examples of the cyclic carbonate compound may include at least one selected from the group consisting of: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, vinylene carbonate, vinyl ethylene carbonate and its halides, or two or more of the above. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).

[0093] Furthermore, specific examples of the linear carbonate compounds may representatively include, but are not limited to, at least one selected from the group consisting of: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or slurries of two or more thereof. In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, are high-viscosity organic solvents with high dielectric constants, thus enabling better dissociation of lithium salts in the electrolyte. When these cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in appropriate ratios, electrolytes with higher conductivity can be prepared.

[0094] Furthermore, the ether in the aforementioned organic solvent may be, but is not limited to, any one selected from the group consisting of: dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether and ethyl propyl ether, or two or more of the above slurries.

[0095] In addition, the esters in the aforementioned organic solvents may be, but are not limited to, any one selected from the group consisting of: methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, or two or more of the above slurries.

[0096] The injection of the non-aqueous electrolyte can be performed at an appropriate stage during the manufacturing process of the electrochemical device, depending on the manufacturing steps of the final product and the required physical properties. That is, such injection can be performed before assembling the electrochemical device or in the final stage of assembling the electrochemical device.

[0097] In the case of the lithium secondary battery according to the present invention, in addition to the winding process as a general process, the separator and electrode can be laminated or stacked and folded.

[0098] Furthermore, there are no particular limitations on the shape of the battery casing; it can be of various shapes, such as cylindrical, stacked, square, pouch-shaped, or coin-shaped. The structure and manufacturing methods of these batteries are well known in the art, and therefore their detailed description will be omitted.

[0099] Furthermore, the lithium secondary batteries can be classified into various types of batteries based on the positive / negative electrode materials used, such as lithium-sulfur secondary batteries, lithium-air batteries, lithium-oxide batteries, and lithium all-solid-state batteries.

[0100] Furthermore, the present invention provides a battery module comprising the lithium secondary battery as a unit cell.

[0101] The battery module can be used as a power source for medium to large-sized devices that require high-temperature stability, long cycle life, and high capacity.

[0102] Examples of the medium to large-sized devices may include, but are not limited to: power tools powered and driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric motorcycles, including electric bicycles (E-Bikes) and electric scooters (E-Scooters); electric golf carts; and energy storage systems.

[0103] Preferred embodiments are presented below to aid in understanding the invention, and the following embodiments are merely illustrative of the invention. It will be apparent to those skilled in the art that various changes and variations can be made within the scope and spirit of the invention, and such changes and variations are natural within the scope of the appended claims.

[0104] Example 1: Manufacturing of negative electrode for lithium-sulfur secondary batteries and lithium-sulfur secondary batteries

[0105] (1) Manufacturing of the negative electrode

[0106] Lithium was heated to 500°C to produce molten lithium. After adding LiNO3 powder to the molten lithium, the mixture was stirred while maintaining the temperature at 500°C. The stirred melt was then cooled to prepare lithium ingots containing LiNO3.

[0107] A negative electrode in the form of lithium foil was manufactured by extruding and rolling lithium ingots containing LiNO3. In the prepared negative electrode, lithium foil was set at 98% by weight and LiNO3 at 2% by weight.

[0108] (2) Manufacturing of lithium-sulfur secondary batteries

[0109] (2-1) Positive electrode

[0110] Sulfur and carbon nanotubes, which are carbon materials, were mixed in a weight ratio of 70:30 and then heat-treated at 155°C for 30 minutes to prepare a sulfur-carbon composite material.

[0111] 90% by weight of the sulfur-carbon composite material, 5% by weight of Danka Black as a conductive material, and 5% by weight of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC = 7:3 (wt / wt)) as a binder were mixed and dissolved in water to prepare a slurry for the positive electrode with a certain concentration (20% relative to the solids).

[0112] The positive electrode slurry was applied to an aluminum current collector, dried at 50°C for 12 hours, and then pressed using a roller press to form a positive electrode active material layer, thereby manufacturing the positive electrode. The prepared positive electrode had a loading capacity of 5.4 mAh / cm³. 2 The porosity is 68%.

[0113] (2-2) Electrolyte

[0114] The following mixed solution was used as the electrolyte: a mixed solution obtained by dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) in an organic solvent consisting of 1,3-dioxolane and dimethyl ether (DOL:DME = 1:1 (volume ratio)).

[0115] (2-3) Manufacturing of lithium-sulfur secondary batteries

[0116] After stacking the negative electrode, the separator, and the positive electrode, 0.1 ml of electrolyte was injected to prepare a lithium-sulfur secondary battery. A porous polyethylene membrane (thickness: 20 μm, porosity: 68%) was used as the separator.

[0117] Comparative Example 1

[0118] The lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that lithium foil without LiNO3 was used as the negative electrode.

[0119] Comparative Example 2

[0120] The lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the negative electrode was generated by applying LiNO3 to the surface of the lithium foil to form a coating.

[0121] Experimental Example 1: Shape and Composition Analysis of Lithium Foil

[0122] The shape of the lithium foil containing LiNO3 in Example 1 and the shape of the lithium foil in Comparative Example 1 were observed, and their composition was analyzed.

[0123] Figure 1 The image shown is a scanning electron microscope (SEM) image of the lithium foil containing LiNO3 prepared in Example 1. The SEM image was taken using a SEM device (JEOL Ltd., JSM-7610F).

[0124] Reference Figure 1 It can be seen that the surface shape of the lithium foil containing LiNO3 is similar to that of ordinary lithium foil without LiNO3.

[0125] Figure 2 Energy-dispersive X-ray spectroscopy (EDS) results of the lithium foil containing LiNO3 prepared in Example 1 are shown. The EDS device was connected to a SEM, and a SEM device (JEOL Ltd., JSM-7610F) was also used as an optional feature of the SEM for component analysis.

[0126] Reference Figure 2 As can be seen from the EDS results of the lithium foil containing LiNO3 in Example 1, N was detected. Furthermore, it can be confirmed that carbon (C), oxygen (O), and silicon (Si) are distributed on the surface of the negative electrode prepared in Example 1. However, the components carbon (C), oxygen (O), and silicon (Si) are also observed on existing lithium surfaces.

[0127] Therefore, it can be seen that since LiNO3 is distributed on the surface of the negative electrode prepared as in Example 1, nitrogen (N) is distributed on the surface of lithium in the form of LiNO3.

[0128] Table 1 below shows the inductively coupled plasma (ICP) analysis results of the lithium foils prepared in Example 1 and Comparative Example 1, respectively. Analysis was performed using an ICP analyzer (PerkinElmer, OPTIMA 7300DV).

[0129] Table 1:

[0130] Comparative Example 1 15 32 5 6 66 5 17 Example 1 3 36 5 8 61 4 3,846

[0131] As shown in Table 1 above, it can be seen that a large amount of N was detected in the lithium foil containing LiNO3 prepared in Example 1.

[0132] Experimental Example 2: Life Performance Evaluation

[0133] 2-1. Lifetime Performance Evaluation of Lithium-Lithium Batteries

[0134] A lithium-lithium battery was prepared in which the lithium foil containing LiNO3 from Example 1 was configured as the negative and positive electrodes. The electrolyte and separator were the same as in Example 1.

[0135] The lithium foil of Comparative Example 1 was used to manufacture a lithium-lithium battery in the same manner.

[0136] For the lithium-lithium batteries manufactured using the lithium foil of Example 1 and Comparative Example 1, with the charge rate and discharge rate set to 1 mA / cm, 2 Then the loop continues.

[0137] Figure 3 This is a graph showing the life performance measurement results of lithium-lithium batteries manufactured using the lithium foils in Example 1 and Comparative Example 1, respectively.

[0138] Table 2 below shows the lithium efficiency (η) calculated using Formula 1, based on the measured life performance of the lithium-lithium battery:

[0139] <Formula 1>

[0140]

[0141] Where Q1 is the total capacity of the lithium foil (mAh), Q S The capacity used during charging / discharging (mAh) is n, and the number of cycles is n.

[0142] Table 2:

[0143] Comparative Example 1 97.82% Example 1 99.56%

[0144] like Figure 3 As shown in Table 2, it has been confirmed that, compared with Comparative Example 1, the lithium-lithium battery containing the lithium foil with LiNO3 of Example 1 has lower overvoltage, stable life performance and good lithium efficiency.

[0145] 2-2. Lifetime Performance Evaluation of Lithium-Sulfur Secondary Batteries

[0146] The lithium-sulfur secondary batteries manufactured in Example 1 and Comparative Example 1 were subjected to 120 cycles after the charge rate and discharge rate were set to 0.24 A / g and 0.36 A / g, respectively.

[0147] Figure 4 The graph shows the life performance measurement results of lithium-sulfur secondary batteries manufactured using the lithium foils in Example 1, Comparative Example 1, and Comparative Example 2, respectively.

[0148] Table 3 below shows the capacity retention rate (capacity retention rate @ 120) after 120 cycles, as experimental results for measuring the life performance of the lithium-sulfur battery.

[0149] Table 3:

[0150] Comparative Example 1 28.9% Comparative Example 2 61% Example 1 84%

[0151] like Figure 4 As shown in Table 3, it has been confirmed that the lithium-sulfur secondary battery containing the lithium foil with LiNO3 of Example 1 has better lifespan performance compared with Comparative Example 1 and Comparative Example 2.

[0152] While the present invention has been described above with reference to specific embodiments and accompanying drawings, it is not limited thereto, and it will be apparent to those skilled in the art that various variations and modifications can be made within the scope of equivalence to the technical spirit of the present invention and the appended claims.

Claims

1. A negative electrode for a lithium secondary battery, the negative electrode comprising a lithium substrate and lithium compounds formed on and within the lithium substrate. The lithium compound described herein comprises at least one selected from the group consisting of: LiNO3, LiF, LiCl, Li2S, Li2CO3, and Li2O, and The lithium compound content is greater than 0% by weight and less than 30% by weight relative to the total weight of the lithium substrate.

2. The negative electrode for a lithium secondary battery according to claim 1, wherein the lithium substrate is lithium foil.

3. The negative electrode for a lithium secondary battery according to claim 1, wherein the thickness of the lithium substrate is 5 to 500 mm. m.

4. A method for manufacturing a negative electrode for a lithium secondary battery according to claim 1, the method comprising the following steps: (S1) Lithium ingots are manufactured by adding lithium compounds to molten lithium; and (S2) The lithium ingot is rolled to produce a lithium substrate containing the lithium compound formed on and inside its surface.

5. The method according to claim 4, wherein the lithium compound is a lithium compound powder.

6. A lithium secondary battery, the lithium secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the negative electrode according to claim 1.

7. The lithium secondary battery according to claim 6, wherein the positive electrode comprises sulfur.

8. The lithium secondary battery according to claim 6, wherein the lithium secondary battery is a lithium-sulfur secondary battery.

Citation Information

Patent Citations

  • Porous Lithium Electrode and Method for Manufacturing thereof and Lithium Secondary Battery using the same

    KR1020170011357A